THE CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND STUDENTS’ WRITING ABILITY - Nuril Firdaus; Ayu Nur Wulansari (JETS: Journal of English Teaching Strategies, 2022)
Writing is one of language ability which many students stated it as the most difficult ability. One of the reason is because of the lack of vocabulary. Meanwhile, vocabulary is the most important thing to master in learning language. Therefore this research aimed to find out the correlation between students’ vocabulary mastery and students’ writing ability. The population was 78 students and the sample taken by using Yamane formula were 62 students. This research used quantitative research method. The data was collected through pre-test and post-test. Each test contained 20 questions; ten questions of vocabulary and ten questions of writing. The tests carried out validity, reliability, normality, homogeneity, linearity, and t-test. All tests were counted by SPSS 16.0 application. Based on the descriptive statistics, the mean score of pre-test were 57.74 and the post-test score mean was higher; 78.79. The correlation result was r-count 0.527 > r-table 0.254 with significance value five percent. It meant H0 was rejected and Ha was accepted. Besides, the significance level of this correlation was 0.527; it was included to average level. Based on the finding, the conclusion was there was correlation between students’ vocabulary mastery and students’ writing ability.